The aesthetics of sculptural and functional creativity in the art of carving Sumerian cylinder seals - Farah Hussein Kazem (مجلة فنون البصرة, 2023)
The current research dealt with (the aesthetic of sculptural and functional creativity in the art of carving Sumerian cylindrical seals) through the study of the aesthetic of sculptural and functional creativity in the art of carving Sumerian cylindrical seals and the Sumerian era, so the researcher sought in the first chapter to clarify the research problem, its importance and the need for it, as well as the goal of the research, which It is represented by the following: defines "the aesthetic of sculptural and functional creativity in the art of carving Sumerian cylindrical seals." Then the researcher concluded the aforementioned chapter by defining the terms that are directly related to the title and objectives of the research. As for the second chapter, it included a presentation of the theoretical framework and previous studies. It consisted of two chapters. In the first chapter, it was established that the emergence and development of cylindrical seals in Sumerian society. As for the second topic, it dealt with the Sumerian sculptural creativity of the seals aesthetically and functionally. The third chapter specialized in monitoring the research community and the tool that included collecting information, so samples were adopted from it in an intentional manner, and it amounted to (3) sculptural works that covered the limits of the research by adopting the descriptive analytical approach for the purpose of analyzing it according to the indicators of the theoretical framework of the research that the researcher relied on.